Implementation of Kurikulum Merdeka in Informatics subject at SMP Negeri 1 Katapang - Sandy Achmad Nugraha (Inovasi Kurikulum, 2026)
Curriculum transformation in Indonesia, particularly through the implementation of the Kurikulum Merdeka, responds to educational needs that must adapt to technological advancements and the demands of the digital era. This study aims to analyze the implementation of Kurikulum Merdeka in the Informatics subject at SMP Negeri 1 Katapang, focusing on curriculum adaptation, challenges, and the instructional strategies employed by teachers and students. A descriptive qualitative approach was adopted, utilizing in-depth interviews with the Informatics teacher and the vice-principal for curriculum affairs; the data were subsequently analyzed using the Miles and Huberman model to gain an empirical overview of the curriculum's implementation dynamics. The findings indicate that teachers successfully developed instructional innovations, such as Student-Centered Learning, Computer Science Unplugged, and the "Amati-Tiru-Modifikasi" (ATM) method, despite facing administrative hurdles, limited physical learning resources, and discrepancies between intended learning outcomes and actual classroom conditions. Adapting technology usage and fostering teacher collaboration emerged as key strategies for optimizing Informatics instruction. Thus, the implementation of *Kurikulum Merdeka* holds significant potential to strengthen students' digital literacy and computational thinking skills, provided it is supported by creativity, training, and adequate facilities.   Abstrak Transformasi kurikulum di Indonesia, khususnya melalui penerapan Kurikulum Merdeka, menjadi respons terhadap kebutuhan pendidikan yang adaptif terhadap perkembangan teknologi dan tuntutan era digital. Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Merdeka pada mata pelajaran Informatika di SMP Negeri 1 Katapang, dengan fokus pada adaptasi kurikulum, tantangan, serta strategi pembelajaran yang diterapkan oleh guru dan murid. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui wawancara mendalam dengan guru informatika dan wakil kepala sekolah bidang kurikulum, kemudian dianalisis menggunakan model Miles dan Huberman untuk memperoleh gambaran empiris tentang dinamika pelaksanaan kurikulum. Hasil penelitian menunjukkan bahwa guru mampu mengembangkan inovasi pembelajaran seperti metode student-centered learning, Computer Science Unplugged, dan Amati-Tiru-Modifikasi (ATM), meskipun dihadapkan pada kendala administratif, keterbatasan media pembelajaran fisik, serta perbedaan antara capaian pembelajaran dan kondisi di lapangan. Adaptasi penggunaan teknologi dan kolaborasi antar guru menjadi strategi utama untuk mengoptimalkan pembelajaran Informatika. Demikian, implementasi Kurikulum Merdeka berpotensi besar untuk memperkuat literasi digital dan kemampuan berpikir komputasional murid, asalkan didukung kreativitas, pelatihan, serta fasilitas yang memadai. Kata Kunci: implementasi kurikulum; Informatika; Kurikulum Merdeka